Internet of Things Smart Sunscreen Station: Descriptive Proof-of-Concept Study - Ford, Helen; Herbert, Jeremy; Horsham, Caitlin; Wall, Alexander; Hacker, Elke (JMIR Publications, 2020)
BackgroundSkin cancer is the most prevalent but also most preventable cancer in Australia. Outdoor workers are at increased risk of developing skin cancer, and improvements in sun protection are needed. Sunscreen, when applied at the recommended concentration (2 mg/cm2), has been shown to block the harmful molecular effects of ultraviolet radiation in vivo. However, sunscreen is often not applied, reapplied sufficiently, or stored adequately to yield protection and reduce sunburns. ObjectiveThe primary aim of this study was to test an Internet of Things approach by deploying a smart sunscreen station to an outdoor regional mining site. MethodsWe deployed a smart sunscreen station and examined the key technological considerations including connectivity, security, and data management systems. ResultsThe smart sunscreen station was deployed for 12 days at a mining workplace (Dalby, Australia). The smart sunscreen station's electrical components remained operational during field testing, and data were received by the message queuing telemetry transport server automatically at the end of each day of field testing (12/12 days, 100% connectivity). ConclusionsThis study highlights that an Internet of Things technology approach can successfully measure sunscreen usage and temperature storage conditions.